2011 IEEE Third International Conference on Privacy, Security, Risk and Trust and 2011 IEEE Third International Conference on S 2011
DOI: 10.1109/passat/socialcom.2011.200
|View full text |Cite
|
Sign up to set email alerts
|

Using Social Sensing to Understand the Links between Sleep, Mood, and Sociability

Abstract: Abstract-In recent years, reality mining experiments have provided several novel insights into human social behavior that would not have been possible without the novel use of smartphone sensing. In this work, we leverage the latest reality mining experiment to study social behavior from a public health perspective. In particular, we focus on sleep and mood as they have a considerable public health impact with serious societal and significant financial effects. We endeavor to explore and uncover the associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 41 publications
2
60
0
Order By: Relevance
“…In this work, we utilize physical activity as the behavioral input due to the large body of research that supports that there is a strong relation of mental wellbeing with activity levels and sleep [17], [18], [19], [20], [21], [22], [23], [24], [25]. Further there has been a large body of work that has shown that smartphone accelerometer data can be used to sense both physical activity through activity recognition [26], [27], [28], as well as sleep [29], [30].…”
Section: Related Workmentioning
confidence: 99%
“…In this work, we utilize physical activity as the behavioral input due to the large body of research that supports that there is a strong relation of mental wellbeing with activity levels and sleep [17], [18], [19], [20], [21], [22], [23], [24], [25]. Further there has been a large body of work that has shown that smartphone accelerometer data can be used to sense both physical activity through activity recognition [26], [27], [28], as well as sleep [29], [30].…”
Section: Related Workmentioning
confidence: 99%
“…and usage-tracking functions (call and SMS histories etc.). Some studies have worked on the mood or individual trait detection using smart phones [14,15,16,17,18]. Ma et al estimated mood defined from displeasure, tiredness and tensity in daily lives using mobile phone use data and the previous subjective mood state [14].…”
Section: Introductionmentioning
confidence: 99%
“…By combining momentary assessments and sensor data, we found with Emotion Sense (http://emotionsense.org/) that self-reported mood is related to sensed physical activity, and other researchers have found that self-reported mood is related to sensed sociability and sensed sleep. 3 These data also allow analysis of behavior change: students' deteriorating well-being over the course of a university semester can be seen in self-reports of decreased mood but can also be detected through decreases in sensed sociability and sensed physical activity. 4 In a clinical context, information about the links between psychological states and behavior could be used to inform treatment as well as monitor patients' progress.…”
Section: Behavior Monitoringmentioning
confidence: 99%